Frequency of surgical resection after starting neoadjuvant chemoradiotherapy in patients with esophageal cancer: A population-based cohort study. Issue 10 (October 2019) - Borggreve, Alicia S.; van Rossum, Peter S.N.; Mook, Stella; Haj Mohammad, Nadia; van Hillegersberg, Richard; Ruurda, Jelle P.
Abstract: Background: Neoadjuvant chemoradiotherapy (nCRT) for resectable esophageal cancer is accompanied by the risk of treatment-related toxicity. The aim of this population-based cohort study was to provide insight in patients who do not proceed to surgical resection after starting nCRT. Methods: Patients who started nCRT for primary esophageal cancer diagnosed in 2015 and 2016 were selected from the nationwide population-based cancer registry. Outcome measurements included omission from surgical resection, reasons for omission of surgical resection, mortality during nCRT (≤90 days after ending nCRT) and 1-year overall survival. Multivariable logistic regression analyses were performed to identify predictive factors for omission of surgical resection. Results: A total of 1521 patients were included, of whom 215 (14.1%) did not undergo surgical resection after starting nCRT. Age (OR:1.04, 95%CI:1.01–1.06), BMI (OR:0.95, 95%CI:0.90–0.99), WHO performance status (WHO 1: OR:1.62, 95%CI:1.16–2.62 and WHO 2: OR:3.53, 95%CI:1.68–7.41) and clinical N status (cN2: OR:1.57, 95% CI:1.04–2.37 and cN3: OR:2.52, 95%CI:1.14–5.55) were significantly associated with omission from surgery. The most frequently reported reasons for omission from surgery were disease progression (44.3%) and physical functioning (22.8%). During nCRT or within the subsequent waiting period to surgery, 38 patients (2.5%) deceased. One year overall survival of the patients who underwent nCRT followed by surgical resection was 94.9%, and 73.5% in the patients who did not undergo surgical resection following nCRT. Conclusions: One in 7 patients who started nCRT for esophageal cancer do not proceed to surgical resection and have a decreased one year overall survival compared to patients who do proceed to surgical resection. Mortality during nCRT is considerable.